TEACHERS AND STUDENTS’ PERCEPTIONS ON THE IMPLEMENTATION OF K-12 SPIRAL PROGRESSION APPROACH - Igcasama, Raymund Medrano (Sanata Dharma University Yogyakarta, 2021)
This study was conducted to determine the perceptions of the Teachers and Students on the implementation of the K-12 Spiral Progression approach in teaching Secondary Mathematics at Dr. Geronimo B. Zaldivar Memorial School of Fisheries (DGBZMSF). The study utilized the mixed-method design (quantitative-qualitative research design). Interviews, questionnaires, and observation were used to gather data. The data were collected, analyzed, and interpreted using the following statistical tools: frequency, percentage, and medians. The study showed that most teachers and students were in favor of the implementation of the said curriculum. One of the teacher respondents noted that “The K – 12 program will greatly help us develop and upgrade our educational system in the Philippines, so we may be able to compete globally with our students who are fully equipped with the 21st-century skills”, another teacher respondent said, “it provides additional training for the students in preparing for college.” According to a student respondent, “K-12 Program can enhance and learn more or know more about mathematics and others”, another said that “this new curriculum will prepare the students in college and improve the student's skills.” However, they admitted that their performances were much better using the old curriculum. In the qualitative part of the study, the responses were categorized. The study found out that the Spiral curriculum had greatly influenced the curriculum, particularly the content and transitions of subjects, the secondary schools, the learners, and especially the teachers. Based on the findings, teachers were still adapting to the new curriculum. They needed more time and training to master all the fields and learn new teaching strategies because it is challenging to teach something that does not have the necessary mastery. They can teach other branches of their significant subjects without an in-depth discussion because it is not their specialization.